Microbiome profile associated with malignant pleural effusion - Shojaee, S; Sharma, A; Gottel, N; Sanchez, T; Gilbert, JA; Rahman, NM (Public Library of Science, 2020)
Introduction There is ongoing research into the development of novel molecular markers that may complement fluid cytology malignant pleural effusion (MPE) diagnosis. In this exploratory pilot study, we hypothesized that there are distinct differences in the pleural fluid microbiome profile of malignant and non-malignant pleural diseases.